WITH NATURES TO APPEARANCE. PROSECUTION OF PORTRAIT - Yurchenko, O.S. (Pedagogy of Higher and Secondary Education, 2022)
In the article methodical advices which must help students 3 courses right to organize of artistically-graphic faculty prosecution of task on composition are expounded is "Portrait".